Usefulness of Intermediate Amino-Terminal Pro-Brain Natriuretic Peptide Concentrations for Diagnosis and Prognosis of Acute Heart Failure - van Kimmenade, Roland R.J.; Pinto, Yigal M.; Bayes-Genis, Antoni; Lainchbury, John G.; Richards, A. Mark; Januzzi, James L. (The American journal of cardiology, 2006)
Age-stratified cutpoints for aminoterminal pro-brain natriuretic peptide (NT–pro-BNP) concentrations are diagnostic in 83% of all subjects with acute dyspnea. This study analyzed subjects with NT–pro-BNP concentrations between the “rule-out” and “rule-in” cutpoints, the so-called natriuretic peptide gray zone. NT–pro-BNP concentrations, clinical characteristics, and 60-day mortality were studied in 1,256 acutely dyspneic patients from an international multicenter study. Of all subjects, 215 had gray-zone NT–pro-BNP concentrations, 116 of whom (54%) were diagnosed with heart failure (HF). Among these subjects, patients with HF were more likely to be older, to have a history of HF, to be in atrial fibrillation, and to have elevated troponin T concentrations compared with those without HF. In multivariate analysis, the use of loop diuretics on presentation (odds ratio [OR] 3.99, 95% confidence interval [CI] 1.58 to 10.1, p = 0.003), paroxysmal nocturnal dyspnea (OR 4.50, 95% CI 1.31 to 15.4, p = 0.02), jugular venous distention (OR 3.05, 95% CI = 1.06 to 8.79, p = 0.04), and the absence of cough (OR 0.18, 95% CI 0.06 to 0.52, p = 0.001) were associated with a diagnosis of acute HF in gray-zone patients. Subjects with HF and diagnostically elevated NT–pro-BNP concentrations had the highest mortality rates, subjects without HF and NT–pro-BNP concentrations <300 ng/L had the lowest mortality rates, and subjects with gray-zone NT–pro-BNP had intermediate outcomes, irrespective of their final diagnoses. Adding specific clinical information to NT–pro-BNP improves diagnostic accuracy in subjects with intermediate NT–pro-BNP concentrations. Mortality rates in subjects with intermediate NT–pro-BNP concentrations are lower than in those with NT–pro-BNP concentrations diagnostic for HF but are higher than in subjects with NT–pro-BNP concentrations less than the gray zone.